IP multicast with applications to IPTV and mobile DVB-H - Minoli, Daniel, 1952- (Wiley, 2008)
Get a clear picture of IP Multicast applications for delivering commercial high-quality video services. This book provides a concise guide to current IP Multicast technology and its applications, with a focus on IP-based Television (IPTV) and Dig.